The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fimmu.2021.661338
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR Deficiency in Monocytic Myeloid-Derived Suppressor Cells Protects Mouse Cardiac Allografts by Inducing Allograft Tolerance

Abstract: BackgroundMyeloid-derived suppressor cells (MDSCs) can prevent allograft rejection and induce immune tolerance in transplantation models. Previous studies have demonstrated that inhibition of mTOR signaling can enhance the MDSC protective effect in heart transplantation (HTx) by promoting MDSC expansion. In addition, mTOR inhibition is related to autophagy. The present study investigated the protective mechanism of mTOR-deficient monocytic MDSCs (M-MDSCs) in mouse HTx.MethodsMyeloid-specific mTOR conditional k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Autophagy was also reported to be required for maintaining tolerance via augmenting survival and function of Tregs 11,12 . Several reports also demonstrated that defective of autophagy in host dendritic cell accelerated graft‐versus‐host disease (GVHD), 13,14 while induction of autophagy prolonged the survival of allografts, including skin allografts, 15 liver allografts 16 and heart allografts 17‐19 . Furthermore, our results demonstrated that RAPA‐nano micelle ophthalmic solution significantly prolonged the survival of corneal allografts, 20 suggested the possible involvement of autophagy in corneal transplantation rejection.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Autophagy was also reported to be required for maintaining tolerance via augmenting survival and function of Tregs 11,12 . Several reports also demonstrated that defective of autophagy in host dendritic cell accelerated graft‐versus‐host disease (GVHD), 13,14 while induction of autophagy prolonged the survival of allografts, including skin allografts, 15 liver allografts 16 and heart allografts 17‐19 . Furthermore, our results demonstrated that RAPA‐nano micelle ophthalmic solution significantly prolonged the survival of corneal allografts, 20 suggested the possible involvement of autophagy in corneal transplantation rejection.…”
Section: Introductionsupporting
confidence: 59%
“…11,12 Several reports also demonstrated that defective of autophagy in host dendritic cell accelerated graft-versus-host disease (GVHD), 13,14 while induction of autophagy prolonged the survival of allografts, including skin allografts, 15 liver allografts 16 and heart allografts. [17][18][19] Furthermore, our results demonstrated that RAPA-nano micelle ophthalmic solution significantly prolonged the survival of corneal allografts, 20 suggested the possible involvement of autophagy in corneal transplantation rejection. However, whether the increased autophagic influx contributes to the prolonged survival of corneal allografts remains inconclusive.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…To validate previously published findings from RNA sequencing data, we performed gene expression profiling using the microarray technique. C57/Bl6 mice were implanted with E0771 cells subcutaneously on the left flank and were treated with either PBS (n = 5) (Figure 2C) [27]. Asper our previous publications, microarray analysis showed that FEC + oHSV-1 therapy increased the genes associated with the B cell receptor signaling pathways.…”
Section: Fec + Ohsv-1 Upregulates Inflammatory Myeloid Cell Pathwaysmentioning
confidence: 53%
“…This switch is characterized by STAT5 and STAT3 signaling with a strong inflammatory response and the upregulation of genes associated with apoptosis. Gene-set enrichment analysis also revealed a strong downregulation of MTORC1 signaling, a known driver of myeloid cell differentiation to the immunosuppressive MDSC phenotype ( Figure 2 C) [ 27 ]. Asper our previous publications, microarray analysis showed that FEC + oHSV-1 therapy increased the genes associated with the B cell receptor signaling pathways.…”
Section: Resultsmentioning
confidence: 99%